Competitiveness Analysis of Nongfu Spring - Zhuoyang Zhang; Jinxin Li; 최명철; 김한얼; Zhaoqi Li (International Journal of Advanced Culture Technology(IJACT), 2025)
This study focuses on Nongfu Spring Co., Ltd., exploring its growth trajectory and strategic initiatives. As a leading player in Chinese beverage industry, Nongfu Spring has achieved remarkable growth since its founding in 1996, transforming from a regional brand into a market leader through sharp brand positioning and continuous product innovation. The research systematically examines the company's key milestones— from its breakthrough in the bottled water market to building a diverse product portfolio. It highlights strategic decisions such as the shift toward natural water, brand image upgrades, and global expansion. Amid intensifying competition and shifting consumer preferences, the study uses SWOT analysis to identify Nongfu Spring's competitiveness, product innovation, and supply chain management, while also addressing challenges like product homogenization, channel integration, and overseas localization. To maintain its competitive edge, the study proposes strategic recommendations, including expanding premium product lines, and tapping into emerging markets. Beyond offering a study on Chinese evolving beverage industry, this research provides practical insights for FMCG companies in crafting sustainable growth strategies.